2002
DOI: 10.1007/s11664-002-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase identification and growth kinetics of the intermetallic compounds formed during in-49Sn/Cu soldering reactions

Abstract: For the application of In-49Sn solder in bonding recycled-sputtering targets to Cu back plates, the intermetallic compounds formed at the In-49Sn/Cu interface are investigated. Scanning electron microscopy (SEM) observations show that the interfacial intermetallics consist of a planar layer preceded by an elongated scalloped structure. Electron-probe microanalyzer analyses indicate that the chemical compositions of the planar layer and the scalloped structure are Cu 74.8 In 12.2 Sn 13.0 and Cu 56.2 In 20.1 Sn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 19 publications
5
27
1
Order By: Relevance
“…6 For the soldering reactions between liquid In-49Sn and Cu substrates, Chuang et al reported the formation of an intermetallic compound Cu 6 (Sn 0.54 In 0.46 ) 5 at the In-49Sn(l)/Cu(s) interfaces. 8 The intermetallic compounds adjacent to the Au/Cu/Al 2 of Cu in liquid Sn (19.5 kJ/mol), as reported by Ma and Swalin. 9 The rate-limiting step in the growth of the (Cu 0.99 Au 0.01 ) 6 Sn 5 intermetallics should be the diffusion of Cu dissolved near the intermetallic reaction front into the surrounding liquid Sn thin film.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…6 For the soldering reactions between liquid In-49Sn and Cu substrates, Chuang et al reported the formation of an intermetallic compound Cu 6 (Sn 0.54 In 0.46 ) 5 at the In-49Sn(l)/Cu(s) interfaces. 8 The intermetallic compounds adjacent to the Au/Cu/Al 2 of Cu in liquid Sn (19.5 kJ/mol), as reported by Ma and Swalin. 9 The rate-limiting step in the growth of the (Cu 0.99 Au 0.01 ) 6 Sn 5 intermetallics should be the diffusion of Cu dissolved near the intermetallic reaction front into the surrounding liquid Sn thin film.…”
Section: Resultsmentioning
confidence: 57%
“…9 The rate-limiting step in the growth of the (Cu 0.99 Au 0.01 ) 6 Sn 5 intermetallics should be the diffusion of Cu dissolved near the intermetallic reaction front into the surrounding liquid Sn thin film. Chuang et al 8 calculated the activation energy for the growth of h-Cu 6 (Sn 0.54 In 0.46 ) 5 intermetallics during the soldering reactions between liquid In-49Sn and Cu substrates and found it to be 28.9 kJ/mol, which, by comparison, was also nearly the same for the growth of h-(Cu 0.99 Au 0.01 ) 6 (Sn 0.52 In 0.48 ) 5 adjacent to the Cu/Ti/Si during the thin-film diffusionsoldering reactions in this present study. The result implied that the growth mechanism of the h-Cu 6 (Sn,In) 5 intermetallic phase for thin-film diffusion soldering was not different from that for bulk soldering reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a highmelting seal, not only can the sealed packages be engaged in subsequent soldering steps, but also joint creep resistance and dimensional stability can be improved. Many studies have been carried out on the characterization of the interfacial reaction between a Cu substrate and bulk In-Sn alloy, 3,[10][11][12][13][14][15] where the eutectic solder In-48wt.%Sn is applied on the substrate either by dipping into a molten solder bath 3,10-12 or sandwiching a solder foil. [10][11][12] However, the reaction between Cu and bulk solder should be different from the thin-film case because in the latter case there is only a limited amount of solder material in contact with the substrate and the chemical composition in the solder layers is inhomogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of the In-48Sn solder joint has been limited in MEMS and MOEMS systems. The OSP surface finish has several advantages, such as its good wetting property, low cost and simple processing steps, while the In-Sn/Cu system exhibited fast IMC growth to consume the Cu layer rapidly [8]. The In-Sn/ENIG solder joint may provide the key to successful application of In48Sn solder, due to its thin Au layer, while the Ni 3 P formed at the interface between Ni 3 (Sn,In) 4 IMC and Ni-P substrate can weaken the solder joint [9].…”
Section: Introductionmentioning
confidence: 99%